16.3k views
3 votes
Write the equation in standard form: 3x + 1 = 2y

3x + 2y = 1

3x + 2y = –1

3x – 2y = –1

3x – 2y = 1

User Vikujangid
by
4.8k points

2 Answers

5 votes

Answer:

3x+2y=-1

Explanation:

moving the numbers around, the outcome will have to be different

// have a great day //

User StarlitSkies
by
5.1k points
1 vote

Answer:

c) 3x - 2y = -1

Explanation:

Given equation,

→ 3x + 1 = 2y

Conversion into standard form,

→ 3x + 1 = 2y

→ 3x + 1 - 2y = 0

→ 3x - 2y = -1

Hence, option (c) is correct.

User Kashif Siddiqui
by
5.0k points